Ecopedagogics as An Alternative Approach in Developing Social Studies Teaching Materials in Coastal Schools in Jakarta - Yuliani, Shahibah; Disman, Disman; Maryani, Enok; Nurbayani, Siti (LPPM Universitas Pendidikan Mandalika, 2024)
The study explores the urgency of eco-pedagogic as a social study teaching materials approach in Jakarta schools and relevant content lifted in developing social studies teaching materials by eco-pedagogics approach. This research used a qualitative method. The collected data were analyzed using triangulation techniques used the participant observation, FGD, and interview involving 28 social studies teachers at schools in North Jakarta and Kepulauan Seribu. Then, it was processed with device NVivo 12 software. The research results showed that (1) The teacher considered that eco-pedagogic approach became a need for developing social studies teaching materials in coastal schools, (2) Relevant content in eco-pedagogic-based teaching materials covered aspects of sustainability environment coast, utilization of environmental functions, and natural resource management. The development of teaching materials was carried out by considering the learning objectives that include evaluation of coastal and marine resource potential, designing solutions to environmental problems, and argument presentation. The proposed learning model in teaching materials was Project-based Learning. In conclusion, the development of ecopedagogy-based teaching materials is very needed as an environmental conservation effort, because in previous research there were no teaching materials that focused on coastal and marine environments. Then, the content contained in social studies teaching materials is eco-pedagogically based with a project-based learning model can be an enriching reference for students at coastal junior high schools in Jakarta focusing on relevant content and using appropriate learning models is expected that students can understand better and care about the coastal and marine environment.